15-Deoxy-γ12,14-prostaglandin J2 Reduces Liver Impairment in a Model of ConA-Induced Acute Hepatic Inflammation by Activation of PPARγ and Reduction in NF-κB Activity - Kan Chen; Jingjing Li; Junshan Wang; Yujing Xia; Weiqi Dai; Fan Wang; Miao Shen; Ping Cheng; Yan Zhang; Chengfen Wang; Jing Yang; Rong Zhu; et al. (PPAR Research)
Objective. 15-Deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) reduces inflammation and has been identified as an anti-inflammatory prostaglandin in numerous animal models. In this study, we investigated both effects of 15d-PGJ2 and its protection mechanism in concanavalin A- (ConA-) induced autoimmune hepatitis in mice. Materials and Methods. In vivo, Balb/C mice were injected with ConA (25 mg/kg) to induce acute autoimmune hepatitis, and 15d-PGJ2 (10 μg or 25 μg) was administered 1 h before the ConA injection. The histological grade, proinflammatory cytokine levels, and NF-κB and PPARγ activity were determined 6, 12, and 24 h after the ConA injection. In vitro, LO2 cells and RAW264.7 cells were pretreated with 15d-PGJ2 (2 μM) 1 h before the stimulation with ConA (30 μg/mL). The NF-κB and PPARγ activity were determined 30 min after the ConA administration. Results. Pretreatment with 15d-PGJ2 reduced the pathological effects of ConA-induced autoimmune hepatitis and significantly reduced the levels of cytokines after injection. 15d-PGJ2 activated PPARγ, blocked the degradation of IκBα, and inhibited the translocation of NF-κB into the nucleus. Conclusion. These results indicate that 15d-PGJ2 protects against ConA-induced autoimmune hepatitis by reducing proinflammatory cytokines. This reduction in inflammation may correlate with the activation of PPARγ and the reduction in NF-κB activity.